Monitoring Recovery After Pediatric ACL Reconstruction Utilizing Promis. Issue 5 (31st May 2022) - Block, Andrew M.; Ganapathy, Aravinda; Nepple, Jeffrey J.
Introduction: Anterior Cruciate Ligament Reconstruction (ACL-R) is increasingly common procedure performed in pediatric and adolescents. Patient-Reported Outcomes Measurements Information System (PROMIS) computer adaptive testing (CAT) has demonstrated to be a valid and reliable means to assess PROs in the pediatric population. Currently, all studies looking at the performance of PROMIS in the ACL-R population have utilized adult cohorts. Purpose: To characterize the recovery after pediatric ACL-R utilizing PROMIS including (1) changes in PROMIS domains during 1-year postoperative period and (2) to investigate if PROMIS scores can identify patients with early signs of arthrofibrosis at 6 weeks postoperatively and deficits in return to play testing at 6 months. Methods: Pediatric patients that underwent ACL-R were prospectively assessed with PROMIS at each clinical visit. PROMIS CAT domains included Mobility and Pain Interference. Inclusion criteria included patients <18 years old who underwent ACL-R with both pre-operative and >6 month PROMIS scores. Time points were as followed: baseline, 1 week, 1 month, 3 months, 6 months, and 1 year. Time points were compared utilizing a mixed-linear regression model. Significance was set at p<0.05. Early signs of arthrofibrosis were identified at 6 weeks postoperatively and defined as flexion less than 90° and lack of full extension greater than 5° regarding best values at physical therapy visits and/or office physical exam. Return to play was assessed via hop testing at 6 months postoperatively with deficits defined as greater than 10% compared to contralateral. Results: The study included 62 ACL-R with a mean age of 14.6±1.9 years. Patients demonstrated significant increases in Mobility and Pain Interference compared to pre-operative values by 3 months postoperatively and continued to significantly improve through 6 months (Figure 1 and 2). Significant improvements from 6 months to 1 year were not seen in either domain (all p>0.05). At 6 weeks postoperatively, 24% of patients had signs of early arthrofibrosis (none ultimately requiring surgical intervention). Significant differences in PROMIS Mobility (29.1 v. 35.1, p=0.001) were present between patients with and without early arthrofibrosis, while differences in Pain Interference were not significant (53.0 vs. 49.4, p=0.15). Patients with deficits on hop testing at return to play had lower PROMIS mobility (48.2 vs. 54.4, p=0.04) and higher PROMIS pain interference (38.9 vs. 33.8, p=0.02) than without deficits. Conclusions: PROMIS domains are easily obtained and demonstrate utility in monitoring pediatric patients after ACL-R including early signs of arthrofibrosis and deficits at return to play testing. Figure 1. Performance of ACL-R patients on PROMIS domains Mobility at the pre-operative, 1 week, 1 month (3 Mo), 6 month (6 Mo) and year time points. Figure 2. Performance of ACL-R patients on PROMIS domains Pain Interface at the pre-operative, 1 week, 1 month, 3 month (3 Mo), 6 month (6 Mo) and year time points.